FEATURES OF VASCULAR ENDOTHELIAL FUNCTIONING IN HEALTHY PERSONS IN DIFFERENT PERIODS OF SOLAR ACTIVITY - Parshina, S. S.; Tokaeva, L. K.; Dolgova, E. M.; Afanas’yeva, T. N.; Strelnikova, O. A. (Одеські астрономічні публікації, 2013)
Functional properties of vascular endothelium in healthy persons had been studied by probe with induced ischemia depending on a solar activity (SA) period during the 23rd solar cycle. The blood viscosity had been estimated before and after occlusion test. The nascency of angiospasm in a low SA is accompanied by adaptive increase of a blood flow property, and in a high SA this mechanism is been losing. So, in healthy persons the period of SA determines functional properties of vascular endothelium.